Waste eggshell membrane-templated three-dimensional CoOx catalyst for efficient low-temperature toluene oxidation with strong thermal stability. Issue 6 (December 2022) - Niu, Kui; Lin, Daifeng; Lan, Wenxin; Feng, Xiaoshan; Gong, Wangyu; Zhang, Zhen; Huang, Baoquan; Luo, Yongjin; Qian, Qingrong; Chen, Qinghua
Abstract: Eggshell membrane was used as the template to synthesize three-dimensional network CoOx catalysts. Besides, hydrogen reduction at 650 °C was adopted to simultaneously remove poisoned sulfur species and produce metal Co, which was self-oxidized on the catalyst surface at room-temperature, accompanied with better reducibility. Compared to counterpart CoOx (direct calcination of C4 H6 CoO4 ∙4 H2 O), CoOx synthesized by using eggshell membrane possesses more Co 3+ and lattice oxygen because its three-dimensional network structure is beneficial to the mass transfer of the reaction. The structure of applied catalyst will be reformed during the oxidation process. Although the active Co species are Co 3+, the spillover of hydrogen from Co 0 to surface leads to a better reducibility of ESM-CoOx, which significantly improves the low-temperature toluene oxidation activity of the catalyst. As a result, ESM-CoOx exhibits a best low-temperature catalytic activity of toluene oxidation (reaching 99% conversion at 250 °C, toluene reaction rate at 225 °C is 2.98 μmol gcat −1 s −1 ). Importantly, the above cobalt catalyst shows excellent thermal stability and 5 vol% water resistance at 250 °C. This work thus provides a novel process to tail highly active CoOx catalyst for low-temperature volatile organic chemicals oxidation in real application. Graphical Abstract: ga1 Highlights: Three-dimensional network structure of ESM-CoOx promotes the mass transfer of reaction. Hydrogen reduction at 650 °C can remove poisoned sulfur species and produce metal Co. Besides to most Co 3+, little reduced Co 0 and Co 2+ are also observed below 250 °C. The relationship between Co evolution and oxidation activity was disclosed. Excellent thermal stability and 5 vol% water resistance at 250 °C was reached.